Konsep Amr dan Mashlahah dalam Perspektif Pendidikan Islam: Kajian Tematik dalam Kitab Waraqat Karya Imam Haramain - Abdur Rouf Hasbullah (Indonesian Journal of Humanities and Social Sciences, 2023)
This article examines the concepts of "Amr" (command) and "Mashlahah" (public good) in the perspective of Islamic education through thematic analysis of the important work "Kitab Waraqat" by Imam Haramain. Amr refers to the guidelines and commands in Islamic teachings that govern the actions of individuals and society. On the other hand, Mashlahah indicates the principle of seeking the public good in making decisions and adapting religious teachings to social contexts. In the context of Islamic education, the study of "Kitab Waraqat" provides deep insight into how the concept of Amr is applied in the process of student character building and teaching ethical values. This concept plays a central role in shaping the personality of students, who are noble and responsible. The study also reveals how the concept of mashlahah is implemented in the formation of educational policies, curriculum development, and the management of educational institutions. This principle of general benefit allows for the adjustment of religious teachings to contemporary needs, thus creating an educational environment that supports the holistic development of students. This article uses thematic analysis to explore the meaning and application of the concepts of Amr and Mashlahah in Islamic education based on the contents of "Kitab Waraqat.â€ The findings highlight the relevance of these concepts in forming the ethical and pedagogical foundations of Islamic education. By linking religious teachings with educational practices, this article illustrates the important contribution of Amr and Mashlahahâ€™s concepts in shaping Islamic education in accordance with Islamic values and meeting the demands of the times.